Transactional and Incremental Type Inference from Data Updates. (2nd September 2016) - Liu, Yu; McBrien, Peter
Abstract: A distinctive property of relational database systems is the ability to perform data updates and queries in atomic blocks called transactions, with the well-known atomicity, consistency, isolation and durability (ACID) properties. To date, the ability of systems performing reasoning to maintain the ACID properties, even over data held within a relational database, has been largely ignored. This article studies an approach to reasoning over data from web ontology language (OWL) 2 RL ontologies held in a relational database, where the ACID properties of transactions are maintained. Taking an incremental approach to maintaining materialised views of the result of reasoning, the approach is demonstrated to support a query and reasoning performance comparable to or better than other OWL reasoning systems, yet adding the important benefit of supporting transactions.